2019
DOI: 10.1038/s41598-019-38832-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and lipidomic plasma profile changes in human participants ascending to Everest Base Camp

Abstract: At high altitude oxygen delivery to the tissues is impaired leading to oxygen insufficiency (hypoxia). Acclimatisation requires adjustment to tissue metabolism, the details of which remain incompletely understood. Here, metabolic responses to progressive environmental hypoxia were assessed through metabolomic and lipidomic profiling of human plasma taken from 198 human participants before and during an ascent to Everest Base Camp (5,300 m). Aqueous and lipid fractions of plasma were separated and analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 75 publications
2
41
0
Order By: Relevance
“…In the present study, however, it could be suspected that the combination of chylomicron remnants delivery and elevated plasma NEFA may have provided enough lipid substrate to drive an increase in hepatic VLDL production. Consistent with this hypothesis, a recent report suggests that journey at altitude may increase the liver output of TG constituted of adipose tissue lipolytic products such as palmitic and oleic acid, supporting the concept that hypoxia may promote lipid recycling and stimulate hepatic TG secretion (O’Brien et al, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, however, it could be suspected that the combination of chylomicron remnants delivery and elevated plasma NEFA may have provided enough lipid substrate to drive an increase in hepatic VLDL production. Consistent with this hypothesis, a recent report suggests that journey at altitude may increase the liver output of TG constituted of adipose tissue lipolytic products such as palmitic and oleic acid, supporting the concept that hypoxia may promote lipid recycling and stimulate hepatic TG secretion (O’Brien et al, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…Another investigation [253], conducted in human subjects which had developed high-altitude pulmonary edema (HAPE) after high altitude exposure, demonstrated that plasma C8-ceramide, sphingosine and glutamine could be used as diagnostic biomarkers for HAPE, suggesting that S1P levels could be used for monitoring adaptation to hypoxia. Finally, a work from 2019 by O’Brien et al [254] on human subjects ascending to Mount Everest Base Camp, identified a decrease in TG alongside an increase in plasma levels of free fatty acids (palmitic, linoleic and oleic acids) and an increase in SM 34:2. Unfortunately, the work did not mention ceramide levels in subjects; this would have been of interest given the increased levels of circulating free fatty acids (in particular palmitate) that are known to be central in ceramide de-novo biosynthesis [57,105,106].…”
Section: Can Environment Influence Sls Levels and Contribute To Obmentioning
confidence: 99%
“…Recent studies have found that people from low altitude to high altitude will cause significant remodeling of tissue metabolism, as well as changes in the level of circulating metabolism ( 9 , 10 ). Hypoxia can inhibit the oxidative metabolism of heart ( 11 ) and skeletal muscle ( 12 ), reduce the ability of fatty acid oxidation ( 13 ), and increase glycolysis ( 14 ) in rodents and non-plateau native people. Based on miRNA and proteomics, we found that Jersey cattle adapt to high-altitude hypoxia by regulating inflammatory homeostasis ( 15 ).…”
Section: Introductionmentioning
confidence: 99%